The specific features of shoulder joint injury and surgical treatment options in patients with rheumatoid arthritis: review of literature - M. V. Panteleev; M. A. Makarov; A. A. Roskidailo (Научно-практическая ревматология)
The review analyzes publications on the specific features of the progression of shoulder joint damage in patients with rheumatoid arthritis (RA) and on the surgical treatment of these patients. Progressive shoulder joint structural changes in RA are accompanied by the formation of articular surface erosions, as well as by damage to the rotator cuff tendons. Several classifications of shoulder joint injuries are described. Reverse shoulder replacement is the surgery of choice in these patients.